Effect of time elapse after wave hitting on coupled spar platform - Saiful Islam, A.B.M.; Jameel, M.; Jumaat, Mohd Zamin (International Journal of Physical Sciences, 2011)
Oil and gas exploration has moved from shallow to much deeper water now-a-days. Offshore compliant floating structure like Spar platforms in this region are competent deep water platform. As water depth increases operational Spar platforms experience more influence of mooring lines suggestively. So the motion analysis of platforms in deep waters requires counting the mooring upshot with spar hull. The most common approach for solving the dynamics of Spar platform is to employ a decoupled quasistatic method, which ignores all or part of the interaction effects between the platform and mooring lines. Coupled analysis in the present study includes the mooring lines and platform in a single model. This model can cope with the coupling conduct and match the forces, displacement, velocities and acceleration at the fairlead position along with all possible significant nonlinearities. The output from such analyses is essentially platform motions as well as a mooring line response. In actual field problems hydrodynamic loads due to wave and currents act simultaneously on Spar platform and mooring lines. In this finite element model, the entire structure acts as coupled in consistent manner. This offshore Spar platform model has been analyzed in regular wave of ocean environment. Surge, heave and pitch motion responses of coupled Spar platform is obtained after 1000 and 6000 s of storm. The behaviors of dynamic responses have been evaluated as noteworthy even for time elapse after wave hitting.